2016
DOI: 10.1136/bmjopen-2015-010138
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs about deceased organ donation in the Arabic-speaking community in Australia: a focus group study

Abstract: ObjectivesTo describe the beliefs and attitudes to organ donation in the Arabic-speaking community.DesignArabic-speaking participants were purposively recruited to participate in 6 focus groups. Transcripts were analysed thematically.Participants53 participants, aged 19–77 years, and originating from 8 countries, participated in 1 of 6 focus groups. Participants identified as Christian (73%), Islam (26%), Buddhist (2%) or did not identify with any religion (2%).Results6 themes (with subthemes) were identified;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
6
32
0
Order By: Relevance
“…Although, this was a qualitative study using focus discussions, it was able to bring out several chalenges to organ donation similar to quantitative studies conducted all over the world [5,6,7,8,11,13,16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, this was a qualitative study using focus discussions, it was able to bring out several chalenges to organ donation similar to quantitative studies conducted all over the world [5,6,7,8,11,13,16].…”
Section: Resultsmentioning
confidence: 99%
“…It was noticed that in case of ambiguity, individuals consider only those views which were followed in their own community as a benchmark for their own views about organ donation. According to a research done in Australia people tend to resort to religion for guidance when they are mostly unfamiliar with organ donation [6]. Intactness of body during burial was found to be an influential belief associated with Muslim as well as Christian religion which impacted their decision negatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this attitude included respecting parental authority, intense emotionality, avoiding taboo, and fearing judgement. 10 A study from Egypt aiming to analyze donor motivations in living-donor liver transplant has shown that all donors had expressed the importance of their religious beliefs in their decision. 11 Some Muslim scholars claim that living-donor organ transplant, extraction of organs from dead individuals, and transplant are prohibited.…”
Section: Organ Donation In Muslim Countriesmentioning
confidence: 99%
“…Lack of knowledge, attitudes, education, gender, occupation, bodily concerns, sociodemographic concerns, community and family beliefs and values, uncertainties regarding religious permissibility, conflict between one's own desire and family values, and desire for reciprocal benefits are some of the reasons that impact an individual's organ donation decision and act as barriers to the process which have been researched by America, Europe, and other countries in the world [2, 3]. …”
Section: Introductionmentioning
confidence: 99%